Thrombus Attenuation Does Not Predict Angiographic Results of Mechanical Thrombectomy with Stent Retrievers - Yilmaz, U.; Roth, C.; Reith, W.; Papanagiotou, P. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Mechanical thrombectomy with stent retrievers in acute stroke has emerged as a promising new technique, with the highest recanalization rate of the therapeutic procedures available thus far. However, in up to 20% of the cases, mechanical thrombectomy with stent retrievers results in poor angiographic outcomes, with Thrombolysis in Cerebral Infarction scores ≤2a. The purpose of this study was to investigate whether thrombus attenuation on the initial CT scan can predict the angiographic outcome of the recanalization procedure in MCA occlusions. MATERIALS AND METHODS: The data of 70 patients with acute MCA occlusions who underwent endovascular treatment with stent retrievers in our department were included. We analyzed thrombus attenuations, angiographic outcome, and periprocedural thrombus fragmentation. RESULTS: The mean thrombus attenuation was 49.8 ± 7.8 HU and the mean difference from the attenuation of the contralateral MCA was 9.9 ± 8.0 HU. There were no significant differences in the thrombus attenuations of occlusions that were successfully recanalized (modified Thrombolysis in Cerebral Infarction ≥2b) and those that were not. Neither were there significant correlations of thrombus attenuations and periprocedural thrombus fragmentations that occurred in 64.3%. We found a nonsignificantly higher rate of recanalizations with modified Thrombolysis in Cerebral Infarction ≥2b when the difference from the attenuation of the contralateral MCA was between 1–20 HU. CONCLUSIONS: In contrast to results of other revascularization procedures as published in a recent study, the angiographic result of mechanical thrombectomy with stent retrievers is not predicted by thrombus attenuation. mTICImodified Thrombolysis in Cerebral InfarctionCAScarotid artery stentingΔTMdifference between thrombus attenuation and attenuation of the contralateral MCA